Degenerate ecocinema: indexing entropy with drones. Issue 3 (27th May 2022) - Fish, Adam
Abstract : The drone both embodies and documents the decay of Earth systems. As a networked computer technology, it is built from metals and minerals extracted from the Earth. As an elevated and mobile camera, it records vast infrastructures, industrial rivers, and mass extinction on the ground below. The drone is a creative tool that comes from and witnesses destruction. This article explores how the drone's form and function indexes degenerate ecocinema through discussion of four drone videos I have recently produced: Points of Presence (2017), on internet infrastructure across North Atlantic islands; Crash Theory (2019), on endangered life throughout the world; Overburden (2022), on hydrocarbon fuel infrastructure in Australia; and Organic Machine (2022), on the labouring Mersey River of Liverpool, UK. This article accompanies an installation of these videos in the Open Eye Gallery's LOOK Climate Lab in Liverpool, UK, January 2022 .